Atypical Endometrial Cells Post-menopause: Case Report - Cardoso, Ana; Alves, Diana; Leite, Paula; Dominguez, Rute (Citotech Online - Case Review, 2016)
The presence of endometrial cells is considered an alarming finding in gynecological smears of women in the second half of the menstrual cycle or after the age of 45 years. In particular, in post- menopausal women, the presence of atypical endometrial cells may represent a serious uterine pathology and requires a thorough evaluation. We report a case of a 77 year post-menopausal woman, who presented with vaginal bleeding without ecographic uterine alterations. Cervicovaginal cytology revealed the presence of abnormal endometrial cells in clusters, unusual in the clinical context of the woman. The cytological result was atypical glandular cells, favor neoplastic. Based on this result, the patient was submitted to an endometrial curettage, which was diagnosed as carcinosarcoma, and with a radical hysterectomy. Although the cytological result was not in accordance with the histological diagnosis, it indicates the necessity of studying the endometrium and the subsequent diagnosis of carcinosarcoma.